Energy-loss contribution to grazing scattering of fast He atoms from a silver surface - Rios Rubiano, Carlos Alberto (2014)
The energy lost by helium atoms axially scattered from a Ag(110) surface is studied in order to investigate the influence of dissipative processes on fast atom diffraction spectra. In this work inelastic projectile distributions are evaluated within a semiclassical formalism that includes dissipative effects due to electron-hole excitations through a friction force. For incidence along the [1-12] and [1-10] directions the model predicts the presence of multiple peaks in the energy-loss spectrum for a given impact energy. But these structures are  completely washed out when the experimental dispersion of the incident beam is taken into account, giving rise to a smooth energy-loss distribution. Simulations including the  experimental energy spread are in fairly good agreement with available experimental data for the [1-12] channel. In addition, our results suggest that inelastic processes produce an almost constant background in the transverse momentum distribution, except in the extremes of the momentum range where classical rainbow maxima appear. By adding elastic and inelastic contributions, experimental diffraction patterns are well reproduced.